Leo Marx's Legacy - Nye , David E. (American Studies in Scandinavia, 2023)
An assessment of Leo Marx’s career, from his youth in New York and Paris, Harvard education, and military service in World War II, to the major themes in his scholarship during 65 years of teaching at Minnesota, Amherst College, and MIT. Best known for his The Machine in the Garden, Marx was one of the founding scholars of American Studies, but he also made seminal contributions to the History of Technology and the environmental humanities. His work is a useful legacy for scholars assessing technological solutions proposed to deal with ecological crises.